PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TWO STAY TWO STRAY( TSTS) UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS V SD NEGERI 184 PEKANBARU - Eny Afrida; Gustimal Witri; Otang Kurniaman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract : This research is motivated by the fact that id found in the class V SD N 184 Pekanbaru, which shows the risult of learning IPS is still relatively is low. Formulation the prolem is this research is: “Doas the aplication of Two Stay Two Stray (TSTS) model can improve learning outcomes in IPS students of SDN 184 Pekanbaru?” This research aim to improve learning out comes in IPS students of SDN 184 Pekanbaru with apllications of learning models two stay two stray (TSTS).The hipotesis in this research of this study is that apllied learning models two stay two stray (TSTS), it can improvelearning out comes in IPS students SDN 184 Pekanbaru. This research was conducted in SDN 184 Pekanbaru in April until June 2016. This from research is classroom action research (PTK)are planned as much as two cycle. The subjectt were students of class V SDN 184 Pekanbaru. Academic year 2015/2016 which amounted to 36 peoples consisting of 14 mens, and 22 womens. Based on the risults of research of teacher activity sheet seen rising each meeting. At the first meeting of the first cycle of 54,16 %, at the fourth meeting of the second cycle 66,67%. And the fifth meeting of the second cycle of 79,17% and the fifth meeting of the second cycle of 87,50%. Masrery learning outcomes to repeat at first cycle increased 10,54% from the based score. The avarage value in the base score 69,05, UH then the first cycle 76,33. In the second cycle 84,03. So that research result are consistent with the hipotesis.Key words : Two Stay Two Stray, Model of Teching .Learning Out Comers